Effect of Yoga on Respiratory Endurance Test in Medical Students (International Journal of Physiology, 2019)
IntroductionYogic practices can be considered to be a very good exercise for maintaining proper health and also has a profound effect on the lung functions of an individual. They are also used as psycho-physiological stimuli to increase the physiological functions and human performance. The present work is undertaken as there was no reported data on comparison of pranayama & suryanamaskar practitioners in various pulmonary endurance functions.Materials & MethodThe present study was conducted at MNR Medical College & Hospital, Sangareddy. The Institute Ethical Committee approved the study protocol. Informed consent was taken from all the subjects. The study was conducted with 80 subjects (aged between 18 to 20 years), under the supervision of a qualified yoga trainer. Inclusion Criteria: Medical students of age between 18–20 years, Only volunteers who are interested in practicing Yoga, Non alcoholic & non smokers. Exclusion criteria: Previous experience of yoga training and physically challenged persons.ResultsThe MVV, 40 mm endurance and chest expansion were significantly increased (p